Delineation of clinical features in Wiedemann–Steiner syndrome caused by KMT2A mutations. Issue 1 (14th April 2015) - Miyake, N.; Tsurusaki, Y.; Koshimizu, E.; Okamoto, N.; Kosho, T.; Brown, N.J.; Tan, T.Y.; Yap, P.J.J.; Suzumura, H.; Tanaka, T.; Nagai, T.; Nakashima, M.; et al.
Abstract : Wiedemann–Steiner syndrome (WSS) is an autosomal dominant congenital anomaly syndrome characterized by hairy elbows, dysmorphic facial appearances (hypertelorism, thick eyebrows, downslanted and vertically narrow palpebral fissures), pre‐ and post‐natal growth deficiency, and psychomotor delay. WSS is caused by heterozygous mutations in KMT2A (also known as MLL ), a gene encoding a histone methyltransferase. Here, we identify six novel KMT2A mutations in six WSS patients, with four mutations occurring de novo . Interestingly, some of the patients were initially diagnosed with atypical Kabuki syndrome, which is caused by mutations in KMT2D or KDM6A, genes also involved in histone methylation. KMT2A mutations and clinical features are summarized in our six patients together with eight previously reported patients. Furthermore, clinical comparison of the two syndromes is discussed in detail.